One soldier's war - Babchenko, Arkadii (New York : Grove Press, 2007)
A young Russian soldier offers a harrowing chronicle of his experiences in the Chechen wars that captures the fear, chaos, hardship, drudgery, and brutality of modern warfare, documenting his personal odyssey from naive, teenage conscript to battle-hardened soldier
Originally published: One soldier's war in Chechnya. London : Portobello Books, 2007
Keywords: Babchenko, Arkadii; Muslims -- Russia (Federation) -- Chehnia; Chechnia (Russia) -- History -- Civil War, 1994- -- Personal narratives, Russian; Chechna (Russia) -- History -- Civil War, 1994- -- Personal narratives